Changes in maternal androgens and oestrogens in mares with experimentally‐induced ascending placentitis. (8th March 2016) - Canisso, I. F.; Ball, B. A.; Esteller‐Vico, A.; Williams, N. M.; Squires, E. L.; Troedsson, M. H.
Summary: Reasons for performing study: While advanced stages of ascending placentitis can be diagnosed by transrectal ultrasonography and clinical signs, early stages can be missed. Thus, additional tools could enhance assessment of placental health. Objectives: To characterise peripheral dehydroepiandrosterone sulphate (DHEA‐S) and testosterone concentrations in mares carrying normal pregnancies (Study 1) and compare plasma concentrations of DHEA‐S, testosterone, oestradiol 17‐β (oestradiol) and oestrone sulphate (OES) in mares with or without placentitis (Study 2). Study design: Longitudinal cohort study of healthy mares (Study 1) and controlled experiment (Study 2). Methods: In Study 1, mares had serum samples collected from 100 days of gestation to term. In Study 2, pregnant mares (260–280 days gestation) were assigned to a control group or a group with placentitis. Placentitis was induced via intracervical inoculation of Streptococcus equi ssp. zooepidemicus . Blood was collected at inoculation/commencement for control mares (day = 0) and daily for 12 days post inoculation (DPI) or until abortion. Steroid concentrations were determined by immunoassays. Concentrations of steroids in Study 2 were also evaluated relative to days from abortion (DFA ‐8 days to 0). Results: In Study 1, DHEA‐S peaked by 180 days gestation, while testosterone concentrations were progressively increased from Days 100 to 180 with a plateau until ~240 days and a progressive decline until 290 days of gestation. In Study 2, concentrations of DHEA‐S and testosterone were not significantly different between groups. There were significant effects of time (oestradiol P = 0.0008, OES P = 0.01) and time‐by‐group interactions (oestradiol P<0.001, OES P<0.0001) for oestrogen concentrations. For mares with experimental placentitis, concentrations of oestradiol were significantly reduced at ‐6, ‐2, ‐1 and 0 DFA, while OES concentrations were significantly reduced on the day before abortion (0 DFA). Conclusions: Testosterone and DHEA‐S were increased and varied through pregnancy. Oestrogens but not androgens decreased significantly in mares with experimentally‐induced ascending placentitis.